Genetic distance in coriander (Coriandrum sativum L.) for essential oil yield and yield traits - B Kumar, S P Singh, A K Singh, H P Singh, N K Patra, A Kalra, H B Singh (Journal of Spices and Aromatic Crops, 2002)
Genetic association and distances were assessed in a collection of 15 Indian accessions of coriander, consisting of 8 land races and 7 cultivars, on the basis of seven economic plant traits including essential oil content and oil yield. The study revealed that genetic distance in the material was substantial with the D2 values ranging from 37.4 (between the genotypes C-2 and DH-5) to 1309 (between the genotypes C-1 and RCr-20). The genotypes clubbed into 8 clusters. The genetic diversity was found to be independent of the geographical diversity of the genotypes. Considered together, the results of genetic association and D2 analysis revealed that the variation in seed yield was the most prominent force accounting for both variations in oil yield and genetic distance in the material. The study suggested that improvement in this crop would be possible by exercising selection for oil yield, seed yield and their associated traits viz. oil content and umbellets per umbel. The results of D2 values and cluster means permitted rational selection of 5-33 and C-1, RCr-41 and PD-1, potent genorypes with complementary characters in morphological fitnesses for yield and its associated traits, for effective cross hybridization programme.